Current Concepts: Mallet Finger. (June 2014) - Alla, Sreenivasa R.; Deal, Nicole D.; Dempsey, Ian J.
Loss of the extensor mechanism at the distal interphalangeal (DIP) joint leads to mallet finger also known as baseball finger or drop finger. This can be secondary to tendon substance disruption or to a bony avulsion. Soft tissue mallet finger is the result of a rupture of the extensor tendon in Zone 1, and a bony mallet finger is the result of an avulsion of the extensor tendon from the distal phalanx with a small fragment of bone attached to the avulsed tendon. Mallet finger leads to an imbalance in the distribution of the extensor force between the proximal interphalangeal (PIP) and DIP joints. If left untreated, mallet finger leads to a swan neck deformity from PIP joint hyper extension and DIP joint flexion. Most mallet finger injuries can be managed non-surgically, but occasionally surgery is recommended for either an acute or a chronic mallet finger or for salvage of failed prior treatment.